PERAN PEMBELAJARAN EKSPOSITORI DALAM MENDORONG MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH - Ulfiyatul Fitriyah; Aminatur Rosyidah; Elok Hidayah; Riris Idiawati (JEAS (Journal of Educational and Applied Science), 2025)
This study aims to analyze the role of expository learning in encouraging student learning motivation in Fiqh subjects. The background of this study is the low motivation of students to learn, which has the potential to hinder their understanding of Fiqh material. The research method used is descriptive qualitative with observation, interview, and documentation techniques to collect data from students and Fiqh teachers. The results showed a significant change in students' learning motivation after the application of the expository method. Students became more active, enthusiastic, and showed increased participation in learning Fiqh. The systematic and clear application of the expository method proved effective in fostering students' interest and enthusiasm for learning. This study recommends the use of the expository method as one of the effective strategies to increase Fiqh learning motivation.